Investigation of Thrust Force and Delamination during Drilling of C/PPS - Masek, Petr; Kolar, Petr; Zeman, Pavel; Vrabec, Martin (Manufacturing Technology Journal, 2016)
Drill bits used for machining of composite materials can have different geometries and it is difficult to choose suitable geometry for a specific type of composite. Unsuitable geometry of a drill bit leads to bad surface quality. The objective of this paper is to find the most suitable drill bit geometry for machining of the thermoplastic composite C/PPS in terms of surface quality and magnitude of thrust force under different cutting conditions. Three drill bits were chosen for experimental investigation. A significant influence of the point angle was identified. A gradually decreased point angle together with an increased rake angle of the cutting edge lead to better surface quality. In addition, investigation of the influence of cutting conditions on surface quality and cutting forces was performed. A considerable influence of feed was observed in comparison to cutting velocity. Information included in this paper can help to design more suitable technology for drilling of thermoplastic composites.
Keywords: FRTC drilling; Drilling tools; Delamination; Cutting forces